Multiple colonization and dispersal events hide the early origin and induce a lack of genetic structure of the moss Bryum argenteum in Antarctica. Issue 16 (5th August 2020) - Zaccara, Serena; Patiño, Jairo; Convey, Peter; Vanetti, Isabella; Cannone, Nicoletta
Abstract: The dispersal routes of taxa with transoceanic disjunctions remain poorly understood, with the potential roles of Antarctica not yet demonstrated. Mosses are suitable organisms to test direct intra‐Antarctic dispersal, as major component of the extant Antarctic flora, with the cosmopolitan moss Bryum argenteum as ideal target species. We analyzed the genetic structure of B. argenteum to provide an evolutionary time frame for its radiation and shed light into its historical biogeography in the Antarctic region. We tested two alternative scenarios: (a) intra‐Antarctic panmixia and (b) intra‐Antarctic genetic differentiation. Furthermore, we tested for evidence of the existence of specific intra‐Antarctic dispersal routes. Sixty‐seven new samples (40 collected in Antarctica) were sequenced for ITS nrDNA and rps4 cpDNA regions, and phylogenetic trees of B. argenteum were constructed, with a focus on its Southern Hemisphere. Combining our new nrDNA dataset with previously published datasets, we estimated time‐calibrated phylogenies based on two different substitution rates (derived from angiosperms and bryophytes) along with ancestral area estimations. Minimum spanning network and pairwise genetic distances were also calculated. B. argenteum was potentially distributed across Africa and Antarctica soon after its origin. Its earliest intra‐Antarctic dispersal and diversification occurred during a warming period in the Pliocene. On the same timescale, a radiation took place involving a dispersal event from Antarctica to the sub‐Antarctic islands. A more recent event of dispersal and diversification within Antarctica occurred during a warm period in the Pleistocene, creating favorable conditions also for its colonization outside the Antarctic continent worldwide. We provide evidence supporting the hypothesis that contemporary populations of B. argenteum in Antarctica integrate a history of both multiple long‐range dispersal events and local persistence combined with in situ diversification. Our data support the hypothesis that B. argenteum has been characterized by strong connectivity within Antarctica, suggesting the existence of intra‐Antarctic dispersal routes. Abstract : We analyze the genetic signature of the cosmopolitan moss Bryum argenteum in the Antarctic region and also at global scale. We reconstructed phylogenetic trees of B. argenteum at Antarctic scale applying molecular clock and ancestral areas reconstruction. This species was already occurring in Antarctica soon after its origin. Then, it colonized Antarctica several times during periods of climatic optima. The lack of genetic structure at intra‐Antarctic level could be due to local intra‐Antarctic genetic admixture favored by dispersal following colonization. Intra‐Antarctic dispersion may have occurred involving both the Transantarctic Mountains and the West Antarctic continental coastline